ENHANCING STUDENTS’ UNDERSTANDING OF MATHEMATICAL CONCEPTS THROUGH THE CONCRETE-PICTORIAL-ABSTRACT (CPA) APPROACHIN LEARNING FRACTIONS - Agusta, Erna Sari (ALGORITMA: Journal of Mathematics Education, 2025)
Abstract Conceptual understanding can be demonstrated by students in restating concepts, classifying objects, presenting concepts, selecting and using procedures, and applying concepts in problem-solving. In reality, students of MTsN 28 Jakarta still struggle to solve everyday problems due to their limited conceptual understanding ability. The purpose of this study was to describe the implementation of the CPA (Concrete-Pictorial-Abstract) approach in mathematics learning, as well as to examine the improvement of students' mathematical concept understanding abilities in fraction material with the CPA approach in class VII-F MTs Negeri 28 Jakarta. This study employs a Classroom Action Research (CAR) design conducted in two cycles. Each cycle consists of stages of planning, implementation, observation, and reflection. The research subjects observed in the study were six students from the upper, middle, and lower groups. Data analysis refers to the evaluation of indicators of conceptual understanding abilities, as observed in the research subject's test answers, which are presented through three stages: data reduction, data presentation, and conclusion. The study's results showed that the average test scores increased from Cycle I to Cycle II. Student learning completeness also increased from the Cycle I and Cycle II tests. Thus, the CPA approach can improve students' ability to understand mathematical concepts.   Abstrak Pemahaman konseptual dapat ditunjukkan siswa dalam menyatakan ulang konsep, mengklasifikasikan objek-objek, mempresentasikan konsep, memilih dan menggunakan prosedur, dan mengaplikasikan konsep dalam pemecahan masalah. Pada kenyataannya, siswa MTsN 28 Jakarta masih kesulitan dalam memecahkan masalah sehari-hari karena kemampuan pemahaman konseptual mereka yang terbatas. Tujuan dari penelitian ini adalah untuk mendeskripsikan implementasi pendekatan CPA (Concrete-Pictorial-Abstract) dalam pembelajaran matematika, serta mengkaji peningkatan kemampuan pemahaman konsep matematis siswa pada materi pecahan dengan pendekatan CPA di kelas VII-F MTs Negeri 28 Jakarta. Penelitian ini menggunakan desain Penelitian Tindakan Kelas (PTK) yang dilakukan dalam dua siklus. Setiap siklus terdiri dari tahap perencanaan, pelaksanaan, observasi, dan refleksi. Subjek penelitian yang diamati dalam penelitian ini adalah enam orang siswa dari kelompok atas, menengah, dan bawah. Analisis data mengacu pada evaluasi indikator kemampuan pemahaman konsep, sebagaimana diamati pada jawaban tes subjek penelitian, yang disajikan melalui tiga tahap yaitu reduksi data, penyajian data, dan kesimpulan. Hasil penelitian menunjukkan bahwa nilai rata-rata tes meningkat dari Siklus I ke Siklus II. Ketuntasan belajar siswa juga mengalami peningkatan dari tes Siklus I dan Siklus II. Dengan demikian, pendekatan CPA dapat meningkatkan kemampuan siswa dalam memahami konsep matematika.